Study of groundwater pollution by leachate using the least-square smoothness-constraints inversion method geoelectric resistivity of configuration schlumberger in case study of final waste disposal (TPA) Air Dingin - Yosi Permata Sari (Department of Physics – Universitas Negeri Padang UNP, 2014)
The final processing place of waste that open,in generally result leachate. The leachate uncontrolled will leak everywhere, so that can affect condition of groundwater around the landfill. The aim of this research is to determine contaminantion of groundwater by leachate in that area. This research use resistivity geoelectrical method with Schlumberger configuration. Data are colected in four track by ARES (Automatic Resistivity meter). Data are interpreted by the Smoothness Constraints Least Squares inversion method to obtain models of 2D the earth's surface. The result of this research showed that there has been contamination of groundwater by leachate in Air Dingin landfilling. Groundwater contamination occurs on every track measurement, except on track 2. Contamination was identification in the depth of 5,00-23,30 m with resistivity value less 10 Ωm.